Borderlands: The new mestiza - Anzaldúa, Gloria (Spinsters, Aunt Lute, 1987)
Rooted in Gloria Anzaldúa’s experience as a Chicana, a lesbian, an activist, and a writer, the groundbreaking essays and poems in this volume profoundly challenged how we think about identity. Borderlands/La Frontera remapped our understanding of what a “border” is, seeing it not as a simple divide between here and there, us and them, but as a psychic, social, and cultural terrain that we inhabit, and that inhabits all of us. This twentieth-anniversary edition features new commentaries from prominent activists, artists, and teachers on the legacy of Gloria Anzaldúa’s visionary work
Le texte « La conciencia de la mestiza : Toward a New Consciousness » a été donné en lecture au cours POL4212.
Keywords: amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; féminisme décolonial; identités LGBTQIA2+; lit3220; littérature; mexique; pol4212; premier cycle; queer; régions géographiques; thématiques; états-unis; études littéraires

This bridge called my back: Writings by radical women of color - Moraga, Cherríe; Anzaldúa, Gloria (SUNY Press., 2015)
merged in the last quarter of the twentieth century. Through personal essays, criticism, interviews, testimonials, poetry, and visual art, the collection explores, as coeditor Cherríe Moraga writes, the complex confluence of identities–race, class, gender, and sexuality–systemic to women of color oppression and liberation. Reissued here, forty years after its inception, this anniversary edition contains a new preface by Moraga reflecting on Bridge's living legacy and the broader community of women of color activists, writers, and artists whose enduring contributions dovetail with its radical vision. Further features help set the volume's historical context, including an extended introduction by Moraga from the 2015 edition, a statement written by Gloria Anzaldúa in 1983, and visual art produced during the same period by Betye Saar, Ana Mendieta, Yolanda López, and others, curated by their contemporary, artist Celia Herrera Rodríguez. Bridge continues to reflect an evolving definition of feminism, one that can effectively adapt to and help inform an understanding of the changing economic and social conditions of women of color in the United States and throughout the world.
Première édition 1981. Les textes "La Guëra" de Cherríe L. Moraga et « Lesbianism As an Act of Resistance » de Clark, Cherryl ont été donné en lecture au cours POL4212.
Keywords: 1900-1999; amériques; anthologie; approches et analyses; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; femmes* de couleur; histoire et politique; intersectionnalité; lit3220; littérature; pol4212; pratiques féministes; premier cycle; privilèges; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; témoignage; états-unis; études littéraires

BALLAST • Les identités de frontières de Gloria Anzaldúa - Anzaldúa, Gloria (BALLAST, 2020)
Gloria Anzaldúa est née au Texas en 1942, à la frontière du Mexique. On la connaît notamment, outre-Atlantique, pour l’ouvrage choral1 qu’elle a copublié en 1982 : la première grande tribune des poètesses féministes non-blanches. Fille d’ouvrier, la théoricienne chicana du « mestizaje » (« métissage ») et de la pensée queer n’a eu de cesse de travailler ses concepts à même la ligne de démarcation qui séparait ces deux États frontaliers : une ligne comme une « blessure », disait-elle. Anzaldúa a fait le choix, alors controversé, d’une écriture où se mélangent toutes ses langues : l’espagnol, le nahuatl uto-aztèque et l’anglais. Exilée dans son propre pays, car trop mexicaine ; exilée au sein des luttes de sa communauté, car lesbienne et féministe ; exilée des champs d’études féministes étasuniens, car trop proche de sa culture familiale : Gloria Anzaldúa, disparue en 2004, s’est employée à penser la création d’espaces à même de fortifier ces vécus et ces identités composites. Nous avons publié un portrait d’elle dans notre dernier numéro papier ; nous prolongeons ce texte par une semaine thématique qui lui sera ici consacrée : comment appréhender la question des appartenances à partir de son œuvre, encore méconnue dans l’espace francophone ? Pour commencer, la traduction d’un texte qu’elle a écrit en 1992.
Keywords: amériques; approches et analyses; arts; cours; discipline; fem3100; identités LGBTQIA2+; premier cycle; queer; ressource en ligne; régions géographiques; thématiques; études littéraires